A universal synthesis strategy for single atom dispersed cobalt/metal clusters heterostructure boosting hydrogen evolution catalysis at all pH values. (May 2019) - Yuan, Shuai; Pu, Zonghua; Zhou, Huang; Yu, Jun; Amiinu, Ibrahim Saana; Zhu, Jiawei; Liang, Qirui; Yang, Jinlong; He, Daping; Hu, Zhiyi; Van Tendeloo, Gustaaf; Mu, Shichun
Abstract: The development of a stable, efficient and economic catalyst for hydrogen evolution reaction (HER) of water splitting is one of the most hopeful approaches to confront the environmental and energy crisis. A two-step method is employed to obtain metal clusters (Ru, Pt, Pd etc.) combining single cobalt atoms anchored on nitrogen-doped carbon (Ru/Pt/Pd@Co-SAs/N-C). Based on the synergistic effect between Ru clusters and single cobalt atoms, Ru@Co-SAs/N-C exhibits an outstanding HER electrocatalytic activity. Specifically, Ru@Co-SAs/N-C only needs 7 mV overpotential at 10 mA cm -2 in 1 M KOH solution, which is much better than commercial 20 wt% Pt/C (40 mV) catalyst. Density functional theory (DFT) calculations further reveal the synergy effect between surface Ru nanoclusters and Co-SAs/N-C toward hydrogen adsorption for HER. Additionally, Ru@Co-SAs/N-C also exhibits excellent catalytic ability and durability under acidic and neutral media. The present study opens a new avenue towards the design of metal clusters/single cobalt atoms heterostructures with outstanding performance toward HER and beyond. Graphical abstract: fx1 Highlights: A series of metal clusters anchored on nitrogen-doped carbon materials are designed and synthesized by assistance of ZIFs. The prepared Ru@Co-SAs/N-C exhibits outstanding catalytic ability and durability at all pH values. DFT calculations verify that the synergistic effect between Ru clusters and Co-SAs/N-C contributes to the great HER activity.